OVERVIEW OF THE STATE OF CORPORATE SOCIAL RESPONSIBILITY WITHIN MULTINATIONAL COMPANIES - CODRUŢA DURA; MIHAELA GHICAJANU (Annals of the University of Petrosani: Economics)
In the near future, multinational companies should play a crucial role in supporting and developing a responsible corporate behavior from social, as well as ecological point of view, within the globalization framework. Thus, the process of globalization and liberalization of markets, of goods and services, must be accompanied by the real progress towards an effective system of global governance, with its own social and environmental dimensions. The paper dwells upon the diagnosis of the current state of corporate social responsibility within the international business environment, substantiated on the basis of a study carried out in 2010 by the American scientific and professional organization Business for Social Responsibility (BSR).